AB0099 Neutrophilic Chemoattractants as Well as Monocyte Chemoattractant Protein-1 (MCP-1) and Interleukin (IL-) 6 Are Induced in Synoviocytes Stimulated with IL-17: Implications for the Pathogenesis of Rheumatoid Arthritis. (10th June 2014) - Sato, K.; Ota, M.; Yokota, K.; Mimura, T.
Abstract : Background: We previously reported that helper T (Th) cells that produce interleukin (IL-) 17 by stimulation with IL-23 promote the differentiation of osteoclasts that resorb the bone matrix 1 . This effect was not considered to be a direct one in which IL-17 specifically acted on osteoclast precursors, but rather, an indirect one resulting from the activation of the osteoblasts that support osteoclastogenesis. The induction of osteoclast differentiation factor, RANKL, on osteoblasts is a strong candidate for this mechanism. IL-17 may also play an important role in the pathogenesis of rheumatoid arthritis (RA) by stimulating synoviocytes instead of osteoblasts in this setting. Objectives: We sought to comprehensively analyze the effects of IL-17 on the synoviocytes derived from patients with RA by transcriptome analysis. Methods: Synovial tissues were obtained from RA patients who underwent joint replacement surgery. Synovial cells were isolated and subconfluent cells were cultured for an additional 15 hours in the presence or absence of 10 ng/mL IL-17. Total RNA was extracted and each sample was subjected to GeneChip analysis (Affymetrix). Results: Most of the genes significantly induced by IL-17 were chemokines having a chemotactic effect on neutrophils, such as chemokine (C-X-C motif) ligand 1 (CXCL1). IL-17 also induced monocyte chemoattractant protein-1 (MCP-1), which may be important for the chemotaxis of monocytes, the precursors of osteoclasts. Unexpectedly, the stimulation with IL-17 alone did not induce the expression of RANKL either at the mRNA or protein level. Another notable molecule induced by IL-17 was IL-6. This is important because, as we reported recently, the combination of tumor necrosis factor (TNF) and IL-6 induces osteoclast-like cells with bone resorption activity both in vitro and in vivo 2 . The differentiation of these osteoclast-like cells was inhibited by JAK inhibitor tofacitinib, but not by osteoprotegerin (OPG), a decoy receptor for RANKL. In contrast, the differentiation of osteoclasts was inhibited by OPG, but not by tofacitinib. TNF is produced not only by monocytes/macrophages but also by other cells such as T cells. In fact, since the discovery of Th17 cells, they have been reported to produce TNF as well as IL-17 3 . Taken together, the combination of Th17 cells and synoviocytes may differentiate monocytes into osteoclast-like cells. To estimate the degree of the relative contribution of osteoclast-like cells and conventional osteoclasts to RA related bone damage, clinical data on the effects of new therapeutic reagents such as denosumab, a monoclonal antibody against RANKL, and tofacitinib need to be evaluated. Conclusions: (1) IL-17 induced the production of neutrophilic chemoattractants as well as MCP-1 by synoviocytes derived from RA patients. (2) IL-17 alone did not induce RANKL on synoviocytes. (3) IL-6 was also induced in RA synoviocytes by IL-17. Considering the fact that the combination of IL-6 and TNF differentiates monocytes into osteoclast-like cells, Th17 cells are suggested to be involved in the bone destruction that takes place in RA. References: Sato K et al., J Exp Med. 2006, 203(12) Yokota K et al., Arthritis Rheumatol. 2014, 66(1) Infante-Duarte C et al., J immunol. 2000, 165(11) Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.2785